6-12x-3+3=0

Simple and best practice solution for 6-12x-3+3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-12x-3+3=0 equation:


Simplifying
6 + -12x + -3 + 3 = 0

Reorder the terms:
6 + -3 + 3 + -12x = 0

Combine like terms: 6 + -3 = 3
3 + 3 + -12x = 0

Combine like terms: 3 + 3 = 6
6 + -12x = 0

Solving
6 + -12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -12x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -12x = 0 + -6
-12x = 0 + -6

Combine like terms: 0 + -6 = -6
-12x = -6

Divide each side by '-12'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 5(y-9)-4y=12 | | n*n=2n | | -9x+14x=70 | | 8x+8y-8x+(-8y)=-48+48 | | 1/4t+7=6 | | 3y/4*2y=7y+2.76555234 | | 8(-x-y)=8(-6) | | 36-(3c+4)=2(c+4)+c | | 9x+63=0 | | 2.25/x-3=10 | | -1(-8x-8y)=-1(-48) | | z/4+2=8-z/4 | | -x+6=-x+5 | | 4+1/7x=9 | | y=-x+5-x+6 | | -x+6-x+5=y+y | | 6x^2=49 | | -2y-33y+24y=15 | | y=-3(-4)-12 | | 3=x/-5+4 | | 3=x/5+4 | | -10y+18=-15y-35+5y | | .21x+525=850 | | -3=x/5-3.5 | | m+18.3=-29.45 | | -35x+63x+3x=14 | | 2m^2+8m+16/2m^2-4m | | 3x+(-3y)-3x+(-3y)=-15+45 | | 90.79-65.98= | | -7(1+6f)=18 | | 39.99+25.99= | | -1(3x+3y)=-1(-45) |

Equations solver categories